ORIENTATION TRACKING WITH MEMS INERTIAL SENSORS - Nik Syahrim , Nik Anwar; Anuar , Mohamed Kassim; Mohammad Fahmi , Miskon; Mohd Rusdy , Yaacob (2012)
In many applications orientation tracking needs to be done, for example in inertial navigation, autonomous mobile robot, virtual reality or industries. This paper proposes a method of doing the orientation tracking using MEMS inertial sensors such as accelerometer, gyro and magnetoresistive sensor. The error problems with this type of sensors are discussed. As results, a comparison of measurements between the three sensors is made. Finally a recommendation on how sensor fusion algorithm could be implemented to get an accurate result.